2014
DOI: 10.5539/ijbm.v10n1p172
|View full text |Cite
|
Sign up to set email alerts
|

Causal Relationships among Dimensions of Consumer-Based Brand Equity and Purchase Intention: Fashion Industry

Abstract: Due to the intense competition in market place, customers nowadays are exposed to several brands from across the globe. Building the brand equity becomes an important source of differentiation. It is widely recognized the important role of brand image in establishing brand awareness and brand attitude. Numbers of research are still debating on relationship among the dimensions of brand equity and yet no conclusive decision has been made. The purpose of the research is to investigate the relationship among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
50
1
34

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(94 citation statements)
references
References 34 publications
9
50
1
34
Order By: Relevance
“…De igual forma, diversos estudios (e.g. Wang y Hwang, 2001; Khan et al, 2015) han mostrado la relación existente entre la notoriedad de una marca y la calidad percibida del producto o servicio comercializado.…”
Section: Notoriedad Imagen Y Calidadunclassified
“…De igual forma, diversos estudios (e.g. Wang y Hwang, 2001; Khan et al, 2015) han mostrado la relación existente entre la notoriedad de una marca y la calidad percibida del producto o servicio comercializado.…”
Section: Notoriedad Imagen Y Calidadunclassified
“…ISM Bogasari FM. Hasil ini sesuai dengan hasil penelitian yang pernah dilakukan oleh Wang dan Tsai (2014) dan Khan et al, (2015) mengenai hubungan antara brand image dalam menumbuhkan purchase intention. Semakin baik sebuah brand image baik dari segi intrinsik maupun eksintrik, maka konsumen akan memiliki minat mencoba bahkan membeli (Zeithaml, 1988).…”
Section: Brand Image Terhadap Purchase Intentionunclassified
“…Women are more sensitive to clothing needs and possess a greater clothing awareness than men (Adjei et al, 2006). Khan et al (2015) asserted that brand awareness should be an important aim of marketing program of fashion companies. While Delong et al (2004) considered that if the consumers have knowledge about the brand, they appear to recognize it.…”
Section: Awarenessmentioning
confidence: 99%
“…Fashion involvement was measured by using 6 items from O'Cass's (2000) and (Belton & Clinton, 2007). While for fashion awareness, it was also measured by 6 items from Khan et al (2015) and Wiedmann et al (2009). In order to ensure the fittingness of the instrument it was pilot tested on a sample of students and the results indicated that the instrument is ready for further analysis.…”
Section: Sampling and Data Collection Proceduresmentioning
confidence: 99%